Psychological Correlates of Excessive Healthy and Orthorexic Eating: Emotion Regulation, Attachment, and Anxious-Depressive-Stress Symptomatology - Strahler, Jana; Wachten, Hanna; Neuhofer, Shanna; Zimmermann, Peter (Frontiers in Nutrition, 2022)
Orthorexia nervosa, the pathological obsession with eating healthy, shares risks and significant comorbidity with other mental disorders. Based on a behavioral conceptualization of the overlap, emotion regulation, attachment style, and anxious-depressive-stress symptomatology are prominent but insufficiently researched endophenotypes for orthorexia nervosa. This study aimed at identifying ways in which difficulties in emotion regulation and attachment-related anxiety and avoidance become apparent in orthorexia nervosa and healthy orthorexia. Additionally, the moderating role of anxious, depressive, and stress symptoms was explored. A convenience sample of 399 adults (266 women) completed questionnaires to measure orthorexia nervosa and healthy orthorexia, difficulties in emotion regulation, partnership-related bond, and anxious-depressive-stress symptomatology. The healthy orthorexia subscale was negatively associated with lack of emotional awareness but no other subscale of difficulties in emotion regulation or attachment-related anxiety and avoidance. Orthorexia nervosa scores were positively linked to difficulties in emotion regulation as well as attachment-related anxiety and avoidance. Multiple linear regression indicated non-acceptance of emotional responses and impulse control difficulties to be the strongest predictors for orthorexia nervosa. Both subscales also mediated the effects of attachment style on orthorexia nervosa with anxious-depressive-stress symptomatology moderating some of these effects. Individuals with higher orthorexia nervosa tendencies showed difficulties in emotion regulation, a common feature also of affective and eating disorders. Improvement in understanding the psychological features of orthorexia nervosa can enable a better differentiation from other disorders, advances in the development of treatment approaches and treatment planning, and outlines directions for future research on mechanisms.